Organizational learning as a strategic resource in supply chain management - Θερίος Νικόλαος Γ.; Θερίος Γεώργιος (SPOUDAI Journal of Economics and Business, 2006)
This study considers the potential role of organizational learning as a strategic resource in supply chain management. A model of learning in supply management process is examined using as a sample Greek medium and large size firms of the manufacturing sector. Organizational learning is viewed as a composite construct arising from four tangible indicators: team, systems, learning and memory - orientations. The results indicate that learning has a positive effect on a set of learning consequences, supply management consequences, management consequences, and performance consequences JEL Classification: L19